Strategies to Optimize Management of Outpatient Worsening Heart Failure: A National Consensus from India - Sandeep Seth; Vijay Kumar Chopra; Raja Ram Mantri; Sunil K. Modi; Sanjay Mittal; Jayagopal Pathiyil Balagopalan; Vinayak Aggarwal; Rajiv Mehrotra; Sundeep Mishra; B. S. Vivek; Sanjiv Aggarwal; B. C. Kalmath; et al. (Journal of the Practice of Cardiovascular Sciences)
Background: Worsening heart failure (WHF) is characterized by the progression of symptoms in patients with established HF, necessitating intensified treatment, typically with diuretics. Outpatient (OP) management of WHF offers an alternative to hospitalization, as many patients experience a gradual onset of symptoms, allowing timely intervention. However, OP WHF is often underrecognized and excluded from clinical trials, highlighting the need for structured guidance. This expert consensus aims to address this gap by providing clinical practice recommendations for OP WHF management. Methodology: A panel of Indian cardiologists convened for an expert meeting moderated by a leading cardiologist. Based on clinical evidence, expert insights, and live polling, consensus recommendations were developed. Results: Experts agreed that WHF is defined by symptom worsening despite standard HF therapy, decompensation in chronic HF, and an increase in oral or intravenous diuretic dose. Vericiguat was recognized as suitable for patients with reduced eGFR (<30 mL/min/1.73 m²), unlike angiotensin-converting enzyme inhibitor/angiotensin II receptor blocker/angiotensin receptor-neprilysin inhibitor (ACEi/ARB/ARNi) and digoxin. While ACEi/ARB/ARNi doses may be reduced in WHF with worsening renal function, beta-blockers should be maintained as long as possible. OP management should prioritize early vericiguat initiation alongside rapid HF therapy optimization. About 44% of experts recommended initiating vericiguat at the first follow-up (3–7 days postdischarge), whereas 33.3% preferred it as a last-line option. Management of end-stage heart failure with advanced options like assist devices and transplants is needed with failure of drug therapy, persisting end-organ failure, and repeated hospitalization. Conclusion: This consensus highlights early OP department (OPD)-based recognition of WHF, OPD-based structured HF therapy optimization, and early vericiguat initiation to improve WHF management in outpatient settings.